DEPRESSÃO E ANSIEDADE DE PESSOAS VIVENDO COM HIV/AIDS: DEPRESSION AND ANXIETY OF PEOPLE LIVING WITH HIV (Revista Contexto & Saúde, 2022)
Objective: To analyze the presence of depression and anxiety of people living with HIV/AIDS, as well as the influence of depression on anxiety. Method: Cross-sectional, quantitative study, conducted between january and july of the year 2019. The participants were 100 people living with HIV who received outpatient care at a Hospital for infectious diseases, northeast, Brazil. A socio-demographic questionnaire, Hamilton Depression Scale and Beck anxiety scale were used. There was descriptive and inferential statistical analysis with KRUSKL Wallis tests and T test, considering significant when p ≤ 0.05. Results: It was identified that 64% were men, 70% heterosexual, 50% had between 20 and 30 years and 90% contracted HIV by sexual contact, 42% had depression and 52% had minimal anxiety. The influence of depression on anxiety (p = 0,041) was evidenced, as well as an association between depression and anxiety scores (p = 0.001). Conclusion: The hypothesis that depression influences the anxiety of people with HIV was confirmed.